Co-hydrothermal carbonization of polyvinyl chloride and lignocellulose biomasses for chlorine and inorganics removal. (1st February 2023) - Zhang, Jing; Chen, Yuhan; Xia, Xu; Fu, Binbin; Lin, Chuanjin; Jia, Guangchao; Cui, Xin; Liu, Fang; Zhao, Peitao; Li, Yimin
Graphical abstract: Highlights: Various lignocellulose biomasses are hydrothermally carbonized with PVC. Insoluble lignin affected synergistic interactions, inhibiting chlorine removal. Inorganics removal is always enhanced due to leaching and metathesis reaction. Synergistic index on dechlorination ranged from −20.3% to 19.9%. Synergistic index on inorganics removal ranged from 0.74% to 154%. Abstract: Co-hydrothermal carbonization (co-HTC) of lignocellulose biomass (LB) and chlorinated waste can simultaneously remove organic chlorine and inorganics, however, the interaction mechanisms are unclear owing to the variety of operating conditions and complexity of biomass compositions. Pine, bamboo, corncob, corn stalk, and wheat straw were co-hydrothermally carbonized with polyvinyl chloride (PVC) at the mass ratio of 9:1 for 30 min under 260 °C to explore the fundamental interactions. The synergistic index (SI) of dechlorination efficiency ranged from −20.3 % to 19.9 %, indicating the interaction depended on the content and composition of cellulose, hemicellulose, and lignin in the LB feedstocks. Hydroxyl functional groups in cellulose and soluble lignin dehydration intermediates promoted PVC substitution. The LB fragments prevented PVC aggregation while promoted PVC fragmentation, thereby facilitating dechlorination. The polyaromatic hydrochar derived from insoluble lignin and polymeric hydrochar derived from hemicellulose, cellulose, and soluble lignin can coat the surface of molten PVC and act as significant dechlorination inhibitors. All SI of removal efficiency of inorganics (RE) were positive, ranging from 0.74 % to 154 %, with large variations for different inorganics, indicating that inorganics contents in LB influenced RE significantly. A large amount of water-insoluble/acid-soluble inorganics was removed via a metathesis reaction. Soluble inorganics were dissolved in the process water by HCl leaching.